Miguel Carlos Juan Verstraete. Yper, Flandes, 18-04-1939 ꟷ Mendoza, 17-11-2021 - Calderón de Cuervo , Elena María; Costarelli Brandi, Hugo; Ricardo F.; Martínez Barrera, Jorge; Massini-Correas, Carlos Ignacio; Muñoz Medina, Ceferino; Peretó Rivas, Rubén (Philosophia, 2022)
In memoriam